Meningkatkan Motivasi Belajar Siswa Pada Materi Mengaji Dan Mengkaji Surah At-Tin Melalui Penerapan Reward Dan Punisment Pada Mata Pelajaran PAI Kelas IV UPT SDN 04 Muaro Sako - Mardianis, Mardianis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning motivation of fourth-grade students at UPT SDN 04 Muaro Sako through the application of reward and punishment methods. The research was conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. In Cycle I, it was found that most students were still less active, with only 35% showing participation in the learning process. However, after improvements were made in Cycle II, such as the application of the card soft method and enhancing the classroom atmosphere, student motivation increased significantly, with 98% of students becoming active. The findings of this study suggest that the application of reward and punishment methods can effectively enhance students’ learning motivation